An Empirical Study of the Determinants of Capital Structure for Non-Financial Companies: Evidence from Egypt - Abd El-Aziz, Baher Mohammed Ibrahem Aly (2011)
Rapid development of firms is focused by managers and shareholders. The development progress is characterized by continuous growth in firms‟ productivity, profitability and investment, holding reasonable and manageable rate of financial distress. Improving the financial institutions plays a significant role in spinning a countries‟ developing wheel because financial institutions assist firms to capture more investment opportunities and extend its investment. Therefore, financial decision is the genuine key behind a firm‟s ability to expand its investment and accelerating growth. Pike R. and Neale B. (2006) simplified “cash” as bloodstream in a living body; when finance is major technique for cash to support business investments, finance is consider lifeblood of the business.The financial choice is questionable prediction for any firm. This doubtful expectation materializes the importance of a firms‟ characteristic in determining capital structure pattern. Countless empirical studies on the factors contributing to capital structure have been conducted for developed countries whilst limited studies investigated capital structure determinants for developing countries. This research studies the determinants of capital structure in Egypt, one of the developing countries in Middle East, and in turn verifying if the stylized facts learned from the studies of advanced economies apply solely for these developed markets or whether they have more general suitability. The researchers suggest that developing countries implement institutional aspects such as business risk and tax rate that are obviously different compared to developed economies resulting in different financial patterns.